2001
DOI: 10.1063/1.1332091
|View full text |Cite
|
Sign up to set email alerts
|

Influence of deep level impurities on modulation response of InGaP light emitting diodes

Abstract: The effect of deep level impurities on static and dynamic properties of InGaP-based light emitters grown by all-solid-source molecular-beam epitaxy is analyzed. The improvement of the output power and the decrease in modulation bandwidth induced by the burn-in process are explained by the recombination enhanced annealing of one deep level trap. This assumption is experimentally proven through comparison of small-signal analysis for resonant cavity light-emitting diodes operating at 650 nm and deep level transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 19 publications
(17 reference statements)
2
9
0
Order By: Relevance
“…24 -26 The similarities between the P vacancy in InP and the measured midgap level have been stated previously. 3 Therefore it is concluded that the midgap deep level is the P vacancy.…”
Section: P Vacancy As the Midgap Deep Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…24 -26 The similarities between the P vacancy in InP and the measured midgap level have been stated previously. 3 Therefore it is concluded that the midgap deep level is the P vacancy.…”
Section: P Vacancy As the Midgap Deep Levelmentioning
confidence: 99%
“…2 In a subsequent work it was seen that the center undergoes recombination enhanced annealing ͑REA͒ which could explain the recovery of GaInP quantum well ͑QW͒ lasers during burn-in testing. 3 In our own previous work, we tentatively identified the defect as being related to P vacancies. That identification was based solely on comparisons with other works, mostly involving deep level transient spectroscopy ͑DLTS͒.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, it is also known that the wide range of operating temperature of monolithic multijunction solar cells, from below-zero to over 100°C, can lead to spatial fluctuations of the sublattices. Problem arising from thermal equilibrium is inherent to the so-called annealing effects on the ordered and disordered subcells, resulting in a shift and broadening of the emission spectra [10,11]. Accordingly, a good-understanding of how ordered and disordered subcells behave in response to changes in temperature is necessary for optimizing device performance at any operating temperature [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A promising emitting material for visible red laser emission, such as that used for digital versatile discs ͑DVD's͒ is Ga x In 1Ϫx P, which has been studied in detail. [6][7][8][9][10][11][12] There are several important properties to be controlled: The reversed band offsets of the sandwiched distributed Bragg reflectors ͑DBR's͒ and the optical cavity material and an optimized doping profile are the big challenges from an electronic point of view; the lattice mismatch and the AlAs/Al x Ga 1Ϫx As interfaces are challenges from a crystallographic point of view. 12 An important step to master the formation of VCSEL structures is the tight control over the manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%